Climate change and marine molluscs of the western North Atlantic: future prospects and perils. (7th March 2014) - Saupe, Erin E.; Hendricks, Jonathan R.; Townsend Peterson, A.; Lieberman, Bruce S.; Pearman, Peter
Abstract Aim Numerous studies have examined potential responses of terrestrial biotas to future climate change, but fewer have considered marine realms. We forecast how marine molluscan faunas might respond to environmental change over the remainder of this century. We test the hypotheses that suitable areas will shift northwards for studied species, and that species will show varied responses to future climate change. Location North and South America and the Caribbean. Methods We generated ecological niche models (in GARP and Maxent) for 14 ecologically, economically and potentially medically important mollusc species, using present‐day summaries and future forecasts of climate from the Hadley Centre and known species occurrence data from natural history collections. Niche models were used to forecast potential distributions according to three scenarios of future change for three time slices. Results Northern extremes of suitability are predicted to shift northwards for only three (GARP) or four (Maxent) of the 14 species, whereas the southern edge of suitability is predicted to shift southwards for seven (GARP) and one (Maxent) of the 14 species. When changes in the geographical centroids of suitability are considered, no significant poleward shifts are anticipated for individual species. Instead, half of the study species (many economically important) experience substantial (> 20%) loss of suitable environmental area, even under the lowest‐emission future climate scenario. Furthermore, the direction and magnitude of the response to predicted climate change is species‐specific. Main conclusions We do not find a coherent pattern of areas with suitable environments expanding at high‐latitude range boundaries, with simultaneous contraction at their low‐latitude boundaries. Tropical marine molluscs may thus show varied responses as average temperatures warm. These results contrast with trends among terrestrial and other marine species, which are rapidly shifting their ranges to higher latitudes. Conversely, the differing responses of these species to future warming are consistent with responses of species to past episodes of change, as observed in the fossil record.